THE EFFECT OF CAPITAL STRUCTURE, LIQUIDITY AND OPERATIONAL EFFICIENCY ON THE PROFITABILITY OF CONVENTIONAL BANKS REGISTERED IN INDONESIA STOCK EXCHANGE - Putriani Putriani; Kasmawati Kasmawati; Rani Munika (STIE Bangkinang Publishing, 2021)
This study aims to determine the effect of capital structure, liquidity and operational efficiency in conventional banks listed on the Indonesian stock exchange. The sample of this study used a saturated census sampling technique, namely 28 conventional banks listed on the Indonesian stock exchange. Data collection techniques used were research files and documents. The data analysis technique used is multiple regression analysis with a significant level (α) of 0.05. The results of this study concluded that the F-test variable Capital Adequacy Ratio (CAR), Loan to Deposit ratio (LDR), and Operating Expenses, Operating Income (BOPO) had a positive effect on Retrun On Assets (ROA). And in the t-test, the two variables tested, namely Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR), have a positive effect on Retrun On Assets (ROA), while Operational Expenses (BOPO) have a negative effect on Retrun On Assets (ROA). The closeness of the relationship between the independent variables and the dependent variable is classified as sufficient. The contribution of the independent variable to the dependent variable was 19.4%.